Biofilm and wound healing: from bench to bedside - Aakansha Giri Goswami; Somprakas Basu; Tuhina Banerjee; Vijay Kumar Shukla (European Journal of Medical Research, 2023)
Abstract The bubbling community of microorganisms, consisting of diverse colonies encased in a self-produced protective matrix and playing an essential role in the persistence of infection and antimicrobial resistance, is often referred to as a biofilm. Although apparently indolent, the biofilm involves not only inanimate surfaces but also living tissue, making it truly ubiquitous. The mechanism of biofilm formation, its growth, and the development of resistance are ever-intriguing subjects and are yet to be completely deciphered. Although an abundance of studies in recent years has focused on the various ways to create potential anti-biofilm and antimicrobial therapeutics, a dearth of a clear standard of clinical practice remains, and therefore, there is essentially a need for translating laboratory research to novel bedside anti-biofilm strategies that can provide a better clinical outcome. Of significance, biofilm is responsible for faulty wound healing and wound chronicity. The experimental studies report the prevalence of biofilm in chronic wounds anywhere between 20 and 100%, which makes it a topic of significant concern in wound healing. The ongoing scientific endeavor to comprehensively understand the mechanism of biofilm interaction with wounds and generate standardized anti-biofilm measures which are reproducible in the clinical setting is the challenge of the hour. In this context of “more needs to be done”, we aim to explore various effective and clinically meaningful methods currently available for biofilm management and how these tools can be translated into safe clinical practice.